Audit Committee Characteristics and Sustainability Reporting Quality in Energy and Material Firms: Does Institutional Ownership Matter? - Winitasha Alya Islami; Wiwiek Dianawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the effect of audit committee size and audit committee meeting on the quality of sustainability reporting and the moderating role of institutional ownership in energy and materials companies listed on the Indonesia Stock Exchange during 2021–2024. Sustainability reporting quality has become an important issue as it reflects a company's transparency and accountability in disclosing economic, social, and environmental information. This study employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consists of 490 firm-year observations selected through purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA). The results indicate that audit committee size has a positive effect on the quality of sustainability reporting, while audit committee meeting has no significant effect on the quality of sustainability reporting. Furthermore, institutional ownership has a direct effect on the quality of sustainability reporting and acts as a quasi moderator. Institutional ownership weakens the positive relationship between audit committee size and sustainability reporting quality but strengthens the relationship between audit committee meeting and sustainability reporting quality. These findings suggest that sustainability reporting quality is influenced not only by internal governance mechanisms but also by the interaction between internal and external monitoring mechanisms within the firm.